Efficacy of left atrial low-voltage area-guided catheter ablation of atrial fibrillation: An updated systematic review and meta-analysis - Zhou, Yaqiong; Zhang, Huamin; Yan, Peng; Zhou, Peng; Wang, Peijian; Li, Xiaoping (Frontiers in Cardiovascular Medicine, 2022)
Aims This study aimed to evaluate the efficacy of low-voltage area (LVA)-guided substrate modification catheter ablation in patients with atrial fibrillation (AF). Methods Systematic searches of the PubMed, EMBASE, and Cochrane databases were performed from inception to July 2022 for all available studies. The effect estimates were combined with the Mantel–Haenszel random-effects model. Subgroup analyses, sensitivity analysis, and meta-regression were conducted to explore the sources of statistical heterogeneity. Results A total of 16 studies involving 1942 subjects (mean age: 61 ± 10 years, 69% male) were identified. All studies included patients with paroxysmal AF, non-paroxysmal AF, or both. At a mean follow-up of 18.9 months, patients who underwent LVA-guided substrate modification ablation had significantly higher freedom from all-atrial tachycardia recurrence than patients who underwent control ablation [67.7% vs. 48.9%, risk ratios (RR) 0.64, 95% confidence interval (CI) 0.55–0.76, P < 0.001], with 36% relative risk and 18.7% absolute risk reductions in all-atrial tachycardia recurrence. Subgroup analysis based on AF types demonstrated that the decreased risk of all-atrial tachycardia recurrence was present predominantly in non-paroxysmal AF compared with paroxysmal AF (RR 0.60, 95% CI 0.52–0.69 vs. RR 0.96, 95% CI 0.81–1.13). Conclusion Low-voltage area-guided substrate modification ablation combined with PVI appears to have a significant beneficial effect of improving freedom from all-atrial tachycardia recurrence, especially in patients with non-paroxysmal AF.